2009
DOI: 10.4049/jimmunol.0901537
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Functional Uniqueness of the TNF Receptor-Associated Factor Gene Family in Amphioxus, the Basal Chordate

Abstract: The TNF-associated factor (TRAF) family, the crucial adaptor group in innate immune signaling, increased to 24 in amphioxus, the oldest lineage of the Chordata. To address how these expanded molecules evolved to adapt to the changing TRAF mediated signaling pathways, here we conducted genomic and functional comparisons of four distinct amphioxus TRAF groups with their human counterparts. We showed that lineage-specific duplication and rearrangement were responsible for the expansion of amphioxus TRAF1/2 and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Con- versely, TRAF1, TRAF4 and SARM act as inhibitors in TICAM1-dependent signaling [33][34][35][36]. As amphioxus TRAF2, TRAF3, TRAF4, TRAF6, and SARM were cloned by our group in other studies [37][38][39], we investigated the relationship between these molecules and bbt-TICAM. The results showed that bbtTRAF3, bbtTRAF4, and bbtTRAF6 had no effect on the NF-κB activation mediated by bbtTICAM (Supplementary information, Figure S5A-S5C), while bbtTRAF2 and bbtSARM attenuated the activity of bbtTICAM in a dose-dependent manner ( Figure 7A and 7B).…”
Section: Bbtticam Failed To Interact With Bbttraf3 4 and 6 But Assmentioning
confidence: 99%
“…Con- versely, TRAF1, TRAF4 and SARM act as inhibitors in TICAM1-dependent signaling [33][34][35][36]. As amphioxus TRAF2, TRAF3, TRAF4, TRAF6, and SARM were cloned by our group in other studies [37][38][39], we investigated the relationship between these molecules and bbt-TICAM. The results showed that bbtTRAF3, bbtTRAF4, and bbtTRAF6 had no effect on the NF-κB activation mediated by bbtTICAM (Supplementary information, Figure S5A-S5C), while bbtTRAF2 and bbtSARM attenuated the activity of bbtTICAM in a dose-dependent manner ( Figure 7A and 7B).…”
Section: Bbtticam Failed To Interact With Bbttraf3 4 and 6 But Assmentioning
confidence: 99%
“…To study the transcriptional activity, the fulllength bbtIRFs were inserted into pCMV-BD (Promega). Vectors of bbtMyD88, bbtTRAF6, bbtRel, and bbtp105 have been described in our previous studies (31)(32)(33).…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…The same color box indicated amphioxus IRF genes with close sequence similarity. and immunofluorescence imaging were conducted according to the protocol described previously (31)(32)(33).…”
Section: Culture Of Amphioxus Intestinal Cells and Poly(i:c) Transfecmentioning
confidence: 99%
“…Embryo collection, section in situ hybridization, Southern blot hybridization, RT-PCR analysis, immunofluorescence imaging, transient transfection, luciferase reporter assay, and coimmunoprecipitation (co-IP) were performed as described previously (23)(24)(25). Primers for hybridization probe preparation and RT-PCR are listed in Supplemental Table I.…”
Section: Nuclear Extraction and Emsamentioning
confidence: 99%